2017
DOI: 10.1659/mrd-journal-d-16-00067.1
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Labeled Regional Products: The Experience of the UNESCO Biosphere Reserve Entlebuch

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
(24 reference statements)
0
22
0
1
Order By: Relevance
“…The additional sales volumes achieved through the labelled products lead to an economic added value in the park-region that translates into jobs: For the UNESCO Biosphere Reserve Entlebuch (Switzerland), the only available data so far, park-labelled products generate a remarkable gross added value of US$ 5.8 million in 2014, corresponding to 4% of the jobs in agriculture and forestry or to ca. 1% of all the jobs in the park-region (KNAUS et al 2017). For the UNESCO Biosphere Reserve Rhön (Germany), KRAUS et al ( 2014) further found a strengthening of the regional added-value chains induced by park-labelled products, i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The additional sales volumes achieved through the labelled products lead to an economic added value in the park-region that translates into jobs: For the UNESCO Biosphere Reserve Entlebuch (Switzerland), the only available data so far, park-labelled products generate a remarkable gross added value of US$ 5.8 million in 2014, corresponding to 4% of the jobs in agriculture and forestry or to ca. 1% of all the jobs in the park-region (KNAUS et al 2017). For the UNESCO Biosphere Reserve Rhön (Germany), KRAUS et al ( 2014) further found a strengthening of the regional added-value chains induced by park-labelled products, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Establishing successfully park-labelled products is, however, a complex and lengthy task. It requires a continuous process, supported by the park-management, that builds up trust, credibility and identity among the producers and the customers (KNAUS et al 2017). Furthermore, the products need to be successfully placed on the market, and the consumers need to know and believe in the positive aspects of the product, which requires solid PR and education (KRAUS et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Local markets can be encouraged to brand products from regional and biodiversity-friendly production. A label will inform consumers about biodiversity-friendly products, such as, for example, encouraged in UNESCO biosphere reserves [12].…”
Section: Communities and Local Authorities Havementioning
confidence: 99%
“…Protected areas are a nature conservation instrument and part of the biodiversity strategy of the Swiss government (BAFU 2018), but they can also function as label regions (eg with the label of a ''national park'') and influence regional economic development. A national park label can be a sustainability certification that offers possibilities of supporting new products or services, or of strengthening sales of existing products and merchandising (Boesch et al 2008;Knaus et al 2017). Moreover, protected areas can position economically vulnerable regions as tourism destinations, particularly for ''soft tourism.''…”
Section: Conservation In Switzerlandmentioning
confidence: 99%
“…Another interviewee (I3) expressed a similar doubt about the usefulness of a new national park product label, since there are already other labels on the market-for example organic and protected designation of origin. These 2 statements are part of a contradictory discourse fragment, opposing the fragment built on political and science-based arguments regarding the need for regional economic development (see Knaus et al 2017;M€ uller-Jentsch 2017). Added value Park as a label And in the buffer zone, regional development is priority.…”
Section: Different Discourses Different Languagementioning
confidence: 99%